Effects of Urbanization Expansion on Landscape Pattern and Region Ecological Risk in Chinese Coastal City: A Case Study of Yantai City - Di Zhou; Ping Shi; Xiaoqing Wu; Jinwei Ma; Junbao Yu (The Scientific World Journal)
Applied with remote sensing, GIS, and mathematical statistics, the spatial-temporal evolution characteristics of urbanization expansion of Yantai city from 1974 to 2009 was studied. Based on landscape pattern metrics and ecological risk index, the landscape ecological risk from the landscape pattern dynamics was evaluated. The results showed that the area of urban land increased by 189.77 km2 with average expansion area of 5.42 km2 y−1 from 1974 to 2009. The urbanization intensity index during 2004–2009 was 3.92 times of that during 1974–1990. The land use types of urban land and farmland changed greatly. The changes of landscape pattern metrics for land use patterns indicated that the intensity of human activities had strengthened gradually in study period. The landscape ecological risk pattern of Yantai city shaped half-round rings along the coastline. The ecological risk index decreased with increase of the distance to the coastline. The ratio of high ecological risk to subhigh ecological risk zones in 2009 was 2.23 times of that in 1990. The significant linear relationship of urbanization intensity index and regional ecological risk indicated that the anthropological economic activities were decisive factors for sustainable development of costal ecological environment.